"Love Isn't There in Your Stomach". (14th May 2013) - Nading, Alex M.
<x xml:space="preserve">Abstract</x> Drawing on participant‐observation in Nicaraguan dengue prevention campaigns and a series of semistructured interviews with Nicaraguan health ministry personnel, this article shows how community health workers (CHWs) balanced two kinds of "medical citizenship." In some situations, CHWs acted as professional monitors and models of hygienic behavior. At other times, CHWs acted as compassionate advocates for their poor neighbors. In 2008, Nicaragua's Sandinista government moved to end a long‐standing policy of paying CHWs, recasting them as citizen–volunteers in a "popular struggle" against dengue. Although CHWs approved of the revival of grassroots advocacy, they were hostile to the elimination of compensation. Framing this ambivalence as part of CHWs' desire to serve as "brokers" between the poor and the state, I suggest that attention to medical citizenship provides insight into the sometimes contradictory ways in which CHWs engage the participatory health policies now taking hold in Latin America and elsewhere.